2006
DOI: 10.1118/1.2237453
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical approach to the problem of dose-volume constraint estimation and their impact on the dose-volume histogram selection

Abstract: This paper outlines a theoretical approach to the problem of estimating and choosing dose-volume constraints. Following this approach, a method of choosing dose-volume constraints based on biological criteria is proposed. This method is called "reverse normal tissue complication probability (NTCP) mapping into dose-volume space" and may be used as a general guidance to the problem of dose-volume constraint estimation. Dose-volume histograms (DVHs) are randomly simulated, and those resulting in clinically accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Additionally, for the clinically relevant endpoint of cognitive dysfunction in humans, we do not have clear evidence at this point of a causal link between loss of NSCs or the dose exposure of these cells and the subsequent development of this late effect. Thus, while NTCP models would provide a valuable tool for assessing plan quality and predicting clinical outcomes in this setting, as has been demonstrated in other intensity-modulated radiation therapy treatment settings, we do not have sufficient clinical data at this point to accurately generate these models for this clinical setting (63,(69)(70)(71). These limitations argue strongly in favor of the need for the collection of longer-term data for late neurocognitive function in patients treated with PCI or WBRT and the need for clonogenic studies for human NSCs.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, for the clinically relevant endpoint of cognitive dysfunction in humans, we do not have clear evidence at this point of a causal link between loss of NSCs or the dose exposure of these cells and the subsequent development of this late effect. Thus, while NTCP models would provide a valuable tool for assessing plan quality and predicting clinical outcomes in this setting, as has been demonstrated in other intensity-modulated radiation therapy treatment settings, we do not have sufficient clinical data at this point to accurately generate these models for this clinical setting (63,(69)(70)(71). These limitations argue strongly in favor of the need for the collection of longer-term data for late neurocognitive function in patients treated with PCI or WBRT and the need for clonogenic studies for human NSCs.…”
Section: Discussionmentioning
confidence: 95%
“…The more often navigated high-dose sections of the map that identify risk would therefore serve as a more reliable indicator. [11][12][13] Outlier DVH trajectories and their relation to NTCP distributions can be a source of misrepresentation of the "average" generated map, which presents an issue for further investigation.…”
Section: Ivc1 Limited Samplementioning
confidence: 99%
“…A more recent study 13 has aimed at linking model-based biological response information to DVH trajectories. The purpose was to obtain dose-volume constraint points more suited to heterogeneous organ irradiations by mapping theoretical normal tissue complication probability ͑NTCP͒ values onto dose-volume space.…”
Section: Introductionmentioning
confidence: 99%
“…The second one is that there is no information tabulated about intermediate levels of risk, especially when several DVH points are considered. Although some studies have been carried out; assuming a linear relationship such as in Linear Discriminant Analysis [2], using Principal Component Analysis [3] or neural networks [4]; conclusions highly depend on the assumptions made and are quite uneasy to use in practice. For simplicity reasons, this study is focused on defining a single DVH point, for a single tolerance dose to be found.…”
mentioning
confidence: 99%